Black Students’ Foregrounds: Evolutions, (De)formations, and Connections in Mathematical Identities: Evolutions, (De)formations, and Connections in Mathematical Identities - Ince, Jamaal (TANGRAM - Revista de Educação Matemática, 2025)
This paper is part of a doctoral thesis conducted by the author. The mathematics identities of Black students can be neglected at times. Moreover, the experiences that they have had and are having can influence the ways they come to understand and perceive the importance of mathematics in their present and future. Utilizing the concept of foregrounds, I attempt to learn about the ways Black student in Newark, New Jersey view their environments, their perceptions of mathematics and how this may connect to their thoughts and ambitions of the future. To do so I interviewed several middle school students, their teacher, and researched the backgrounds and foregrounds of the participants and of the city of Newark.